Seismic response analysis of frame with friction damper. Issue 7 (5th August 2019) - Zhang, Min; Wang, Dongzhuo
Abstract : Purpose: This paper aims to study the seismic response of frame structure with friction dampers. Design/methodology/approach: The state equation of the structure subjected to the earthquake is presented and solved, from which the maximum drift and the interlayer drift angle of the floors of the structure subjected to the seismic waves of four types of sites are analyzed. Findings: The result indicates that the damping effect is significant on the floors with the friction damper but is almost little influence on the other floor. Originality/value: The result indicates that the damping effect is significant on the floors with the friction damper but is almost little influence on the other floor.